Hadoop real world solutions cookbook - Owens, Jonathan R. (Packt Publishing, 2013)
Realistic, simple code examples to solve problems at scale with Hadoop and related technologies.
Keywords: Apache Hadoop.; Apache Hadoop; elektronické knihy; electronic books